Concatenated space-time block coding with asymmetric MPSK TCM - AO Jun1; MA Chun-bo1; AO Fa-liang1; LIAO Gui-sheng2 (Tongxin xuebao)
The field of concatenated space-time block coding （inner） with trellis coded modulation （outer） has recently attracted interest as a means of jointly considering the error correction coding gain and diversity gain possible without bandwidth expansion and power expansion over fading channels. A concatenated space-time block coding （STBC）with asymmetric MPSK TCM scheme, based on the design criteria for constructing improved concatenated space-time block coding with TCM, was presented by introducing the new optimal signal point assignment. Analysis and simulation results demonstrate that these concatenated STBC with asymmetric MPSK TCM have better coding gain than traditional concatenated STBC with TCM under the same spectral efficiency, decoding complexity.